2014
DOI: 10.1080/19443994.2014.946721
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the effect on the productivity of cascade-type solar distillation systems with varying cover thicknesses and still orientations under tropical Caribbean climatic conditions

Abstract: To cite this article: Monica K. Boodhan & Indra Haraksingh (2014): An investigation into the effect on the productivity of cascade-type solar distillation systems with varying cover thicknesses and still orientations under tropical Caribbean climatic conditions, Desalination and Water Treatment, Previous investigative work related to solar stills focuses mainly on issues relating to the temperature gradient between the brine and the condensing surface. It is common practice when calculating the efficiencies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…The results of an experiment revealed that while the thickness of the glass cover of a solar still reduces to 3.5 mm, the average output of pure water from the still was 31.13% higher than that from a solar still with a 4 mm thick glass cover [29]. Several experiments were reported on the effect of different glass covers thickness on a solar still performance [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…The results of an experiment revealed that while the thickness of the glass cover of a solar still reduces to 3.5 mm, the average output of pure water from the still was 31.13% higher than that from a solar still with a 4 mm thick glass cover [29]. Several experiments were reported on the effect of different glass covers thickness on a solar still performance [30][31][32].…”
Section: Introductionmentioning
confidence: 99%